Modulation of Streptomycin Killing Rate against Mature Escherichia Coli Biofilms in the Presence of Medicinal Plant Extracts - Z. Y. Samoilova; G. V. Smirnova; O. N. Oktyabrsky (Acta Biomedica Scientifica, 2019)
Background. Medicinal plant extracts exhibiting pro- and antioxidant properties may affect antibiotic-induced killing of biofilm-producing bacteria in both synergistic and antagonistic modes. Better understanding of these alternations is required to adjust antibiotic therapy and herbal medicine in order to exclude unwanted losses of antibiotic efficiency.Aim: to study modulation modes of streptomycin killing rate against mature biofilms of Escherichia coli in the presence of different doses of commonly used medicinal plant extracts.Materials and methods. Pharmacodynamic parameter killing rate and mass biofilm formation were determined in the presence of streptomycin and medicinal plant extracts.Results. Synergism was found between 100 mg/ml streptomycin and low doses (0.83 mg of dry herb/ml) of green, black tea, Arctostaphylos uva-ursi, Betula pendula and Laminaria japonica against killing mature biofilms. Alternatively, high doses (6.64 mg of dry herb/ml) of green, black tea and Vaccinium vitis-ideae demonstrated antagonism, decreasing killing rate and enhancing biofilm formation. Presumably, high doses of the extracts were sufficient to enhance biofilm formation blocking penetration of streptomycin through enlarged biofilm matrix and diminishing the killing rate.Conclusions. Widely consumed as soft beverages or for prophylactic purposes green, black tea and V. vitis-ideae could promote strong antagonistic effects with streptomycin. These extracts can stimulate biofilm production, making benefit for commensal microbiota, but have clinical relevance due to a significant reduction in the lethal efficiency of streptomycin in biofilms of pathogenic strains. This highlights the need of careful antibiotic prescription scheme adjustment when choosing appropriate combinations of plant extracts and antibiotics to achieve a synergistic effect.